Influence of acrylic latex and pre-treated hemp fibers on cement based mortar properties. (1st March 2021) - Candamano, S.; Crea, F.; Coppola, L.; De Luca, P.; Coffetti, D.
Graphical abstract: Highlights: The Ca(OH)2 pre-treatment improves thermal stability of hemp fibers. Hemp fiber-reinforced mortars show higher pre-cracking flexural stiffness values. Treated hemp fiber-reinforced mortars show higher load-carrying capacity. Treated hemp fiber-reinforced mortars show higher energy absorption capacity. Latex and defoamer increase resistance to penetration of fibers-reinforced mortars. Abstract: In this study, authors propose and investigate a strategy aimed to improve the interaction at the fiber–matrix interface, while tailoring matrix resistance to penetration, in hemp fiber-reinforced cement based mortars. It consists of a chemical modification of the hemp fibers carried out through a Ca(OH)2 pre-treatment and of a matrix modification using an acrylic elastomeric polymer dispersion as additive. The effect of the pre-treatment, on the thermal and chemical properties of the hemp fibers, has been investigated using X-ray diffractometry, Fourier-transform infrared spectroscopy, thermogravimetric analysis and scanning electron microscopy. Results showed that chemical pre-treatment is effective in removing hemicelluloses, lignin and waxes thus providing a clean fibers' surface and a higher thermal stability. Fiber-reinforced cement based mortars have been manufactured using pristine and treated 12 mm long hemp fibers at 0.5 wt%, 1 wt% and 1.5 wt% on cement. Their mechanical performance, capillary water absorption and drying shrinkage behavior have been investigated. Hemp fiber-reinforced mortars show a post peak response in flexural tests, being their energy absorption capacity and load-carrying capacity after crack onset positively affected by hemp fibers content and remarkably improved by chemical pre-treatment. Shrinkage behavior of fiber reinforced mortars is characterized by an initial limited expansion that can be associated to fibers swelling due to water absorption. The acrylic latex fills the matrix pores and reduces by 50% the sorpitivity of the composites.